Recent advances and future challenges in gene therapy for hearing loss - Ana E. Amariutei; Jing-Yi Jeng; Saaid Safieddine; Walter Marcotti (Royal Society Open Science, 2023)
Hearing loss is the most common sensory deficit experienced by humans and represents one of the largest chronic health conditions worldwide. It is expected that around 10% of the world's population will be affected by disabling hearing impairment by 2050. Hereditary hearing loss accounts for most of the known forms of congenital deafness, and over 25% of adult-onset or progressive hearing loss. Despite the identification of well over 130 genes associated with deafness, there is currently no curative treatment for inherited deafness. Recently, several pre-clinical studies in mice that exhibit key features of human deafness have shown promising hearing recovery through gene therapy involving the replacement of the defective gene with a functional one. Although the potential application of this therapeutic approach to humans is closer than ever, substantial further challenges need to be overcome, including testing the safety and longevity of the treatment, identifying critical therapeutic time windows and improving the efficiency of the treatment. Herein, we provide an overview of the recent advances in gene therapy and highlight the current hurdles that the scientific community need to overcome to ensure a safe and secure implementation of this therapeutic approach in clinical trials.